Advantages of a Novel Device for Arterial Catheter Securement in Anesthetized Dogs: A Pilot Randomized Clinical Trial - Sasaki, Kazumasu; Shiga, Takuya; Gómez de Segura, Ignacio Álvarez (Frontiers in Veterinary Science, 2019)
Arterial catheters are used for intraoperative continuous direct blood pressure monitoring in dogs. Factors such as bending and occlusion of the cannula are believed to be involved in direct blood pressure measurement failure. However, no method has been proposed to improve the maintenance of arterial catheter patency in veterinary medicine. The aim of this pilot study was to evaluate the patency of arterial catheters when using an arterial catheter securement device in the dorsal pedal artery of dogs under general anesthesia. Client-owned dogs (n = 120) were anesthetized for surgical procedures, during which direct arterial blood pressure was monitored using an arterial catheter secured with conventional film dressing and medical tape. A securement device, allowing an angle of 12.5° to the skin surface of the dorsal pedal area, was used in 50% of the dogs (n = 60). Significant reductions were observed in the frequency of catheter flushing and rate of occlusion in the experimental group compared to the control group (13.3% vs 35.0%, relative risk [RR]: 0.381, 95% confidence interval [CI]: 0.183–0.792, P = 0.001 and 8.3% vs 23.3%, RR: 0.376, 95% CI: 0.145–0.977, P = 0.044, respectively). The Kaplan-Meier curves for assessing the probability of occlusion were significantly different between the groups (P = 0.042). In conclusion, this pilot study suggests that the novel arterial catheter securement device is effective for achieving stable securement of the catheter hub in the dorsal pedal artery and for maintaining a longer duration of arterial catheter patency in dogs under general anesthesia. Therefore, the use of an arterial catheter securement device in the dorsal pedal artery of dogs would be useful for continuous hemodynamic monitoring and improve patient safety when direct arterial blood pressure monitoring is required in dogs undergoing general anesthesia.